Lean management of nursing human resources during COVID‐19 pandemic - Jianghong Tan; Yanzhen Tian; Lang Wang; Yi He; Songli Cui; Chunyan Feng; Anlie Cai (Wiley, 2023)
Abstract Aim To find a rapid, scientific, rational and accurate method of allocating nursing human resources during the COVID‐19 pandemic. Design A longitudinal prospective study. Methods Lean management tool is used to implement four‐level scheduling of nursing human resources, which is departmental level, district level, hospital level and city level, according to the daily reporting data of the whole hospital, such as Lianfan scheduling data, Dingding sensitive data and Hospital Information System daily report data. Results Fifty batches of nursing manpower, 294 nurses and 3813 working days were deployed during the pandemic, and the nursing human resources allocation mathematical models of the hospital and all departments were constructed. Since COVID‐19 occurred, the infection rate of nurses with novel coronavirus and the mortality rate of critical patients have been keeping 0%, and the cure rate of common patients has been 100%. Conclusion The use of lean management tool to allocate nursing human resources plays a positive role in ensuring zero infection of nurses, improving the cure rate of common patients and reducing the mortality rate of critically ill patients with COVID‐19.